PEMBANGUNAN PERANGKAT LUNAK REKAM MEDIS BERBASIS WEB - Wahid Salman Al Farizi; Trismianto Asmo Sutrisno (PSTE UNIMUS, 2017)
Medical record is file which comprising information about patient identity, anamnese, determination of laboratory physical, diagnosa all passed service and medical therapies gave to patient, both for home care and stay care. Computerized medical record depository, make the medical record quick and easy to processed in order to facilitate department of medical record in the processing of medical record data become information in the form of reports and statistical growth of medication service and disease growth statistic. Medical Record software is a software which facility officer of hospital in documenting medical record files, this software can conduct patient data documentation from patient registration in registration department of hospital till patient go out of hospital. This software written in PHPprogramming language, based on object oriented programming technique. Another existing facilities in this software are treatment data of home care patient and stay care patient, drug data and drug stock data and invoice of treatment data. This software also equiped by complete enoughadministrative facility, such as user administration, user group, treatment data, disease data, drugs data, and ward data of hospital. This software also has facility to making of report, such as patient report based on age faction or patient report based on work faction. Based on the development of medical record software, can be concluded that documentation of medical record files in digital form can help to realize administration order at hospital, where medical record software can decrease patient data duplication which enlist at hospital Keywords: Software, Medical Record, Web